Study on stretch-retractable single-section continuum manipulator. (2nd January 2019) - Gao, Guohua; Wang, Hao; Fan, Jinwei; Xia, Qixiao; Li, Lianshi; Ren, Han
ABSTRACT: This paper proposes a stretch-retractable single-section (SRSS) continuum manipulator. Its backbone is composed by a series of springs. Thus, this continuum manipulator owns feature of a large-scale stretch-retractable ability. With such a feature, different from traditional single-section continuum manipulator which distal end moves in a curved surface, the presented manipulator's distal end has a solid work space. The kinematic model including the variable parameter of backbone length was established, and the stretch-retractable workspace was analyzed, with which the driving strategy was proposed. The prototype was made out based on the concept of the large-scale stretch-retractable backbone. The driving patterns with single parameter input and the driving patterns with multi parameter inputs were carried out. The tests verified the presented SRSS continuum manipulator. GRAPHICAL ABSTRACT: